Monte Carlo simulations and forecasting of Radium-226, Thorium-232, and Potassium-40 radioactivity concentrations - Kulahci, Fatih; Akozcan, Serpil; Gunay, Osman (Springer, 2020)
This study depicts the radioactivity time series levels of Ra-226, Th-232, and K-40 prospectively by Monte Carlo simulations (MCSs). Three ARIMA stationary stochastic processes are used with measurement records statistical parameter conservation. The MCSs by means of the ARIMA stochastic processes, the statistical characteristics of the radionuclide data are determined and the future simulation forecasts are made for different periods (time between two measurements, i.e. 1 week). Future concentrations of radionuclides with MCS are estimated for the first time. The results obtained on the transport, control and management of radionuclides can also reach similar gains for other different materials.
Keywords: Monte Carlo; Hypothesis test; Forecasting; Prediction; Model